Conections between platelets amino acids profile and known cardiometabolic risk factors in patients with coronary artery disease and atrial fibrillation - I.O. Melnychuk (Medičnì Perspektivi)
The aim of our work was to identify the relationship between platelet amino acid profile and cardiometabolic risk factors in patients with coronary heart disease and atrial fibrillation. 300 patients were examined, who were divided into 3 groups: the first (I) – 149 patients with coronary artery disease (CAD) and without arrhythmias, the second (II) – 123 patients with CAD and paroxysm of atrial fibrillation (AF) and the control group (CG) – 28 patients without CAD and arrhythmia. The platelets amino acid (AA) profile was determined by ion exchange liquid column chromatography. Cardiometabolic risk factors studied: total cholesterol (TC), triglycerides (TG), low-density lipoprotein (LDL), high-density lipoprotein (HDL), lipoprotein α (Lpα), apolipoprotein A1 (ApoA1), apolipoprotein B (ApoB), C-reactive protein (CRP), interleukin-6 (IL-6), trimethylamine (TMA) and trimethylamine-N-oxide (TMAO). Significant increase of isoleucine (10.73%), leucine (12.63%) and decrease of threonine (23.05%), serine (5.06%), glycine (32.21%), valine (30.83%) levels in platelet AA profile was observed in patients with CAD and AF compared to patients with CAD without arrhythmias, p<0.05. Also, significant increase of apolipoprotein B (29.91%), CRP (40.93%), IL-6 (22.93%), TMA (16.13%) and TMAO (57.54%) and decrease of TMA/TMAO ratio (26.16%) was found in CAD with AF patients compared to CAD patients without arrhythmia, p<0.05. The highest number of correlations was found between platelets AA profile and TMA/TMAO ratio (total number =7), TC (total number =7) and fibrinogen levels (total number =6). In addition, most correlations were found between glycine (total =12), threonine (total =6), glutamate (total =6), valine (total =6), and cardiometabolic risk factors. The level of glycine in platelets is correlated with most cardiometabolic risk factors, such as: age (r=-0.305), BMI (r=-0.351), TC (r=-0.304), LDL (r=-0.348), ApoA1 (r=0.373 ), ApoB (r=-0.347), IL-6 (r=-0.315), TMAO (r=-0.654), TMA/TMAO ratio (r=0.688), prothrombin index (r=0.317), activated partial thromboplastin time (r=-0.365) and fibrinogen level (r=-0.396), p<0.05. So, in our work, the relationship between platelets AA profile and cardiometabolic risk factors in patients with CAD with AF was revealed. According to the results of the correlation analysis with known cardiometabolic risk factors, an important pathogenetic role of the glycine, threonine, valine and glutamate platelets levels in CAD and AF patients was revealed.